A música no segundo Nietzsche - Santos, Felipe Thiago dos [UNESP] (2015)
Human, All Too Human (1878) represents the beginning of the phase in which the Nietzsche philosophy (1844 - 1900) breaks up with their former and major influences: Schopenhauer and, mostly Wagner. Regarding to the art, this destructive time of Nietzsche's philosophy becomes to criticize the musician (genius) deification and the music concept as an ineffable language (expression of the world essence) and / or feelings, ideas that were developed by Romanticism especially by the Richard Wagner composer. Moreover, Nietzsche also criticizes - with some exceptions - another concept present at the time that intends to show the music listening criteria are solely sound relations (formalism), conception defended by Viennese music critic Eduard Hanslick in From Belo Musical (1851). However, the second phase of Nietzschean thought (between 1876- 1882) conceives art not only in a negative way. In the second Nietzsche we can see from a historical musical defended by him in which music, uprooted of misinterpretations about its effects and contents can support life while an affirming experience. Therefore, first of all our goal will be to expose, from Nietzsche criticism presents in its second phase to the design of music present in his time, a music philosophy with own characteristics. Secondly, we will show that even in its second phase, this philosophy uses music to point out a singular experience, such as man affirmation against the world. For the enjoyment of our goals, we will analyze both works of the second phase of Nietzsche as posthumous unpublished in addition to dialogue with Brazilian and foreign commentators.